Coping mechanisms for technostress through social support among librarians in Indonesian public libraries - Galih Pramudya, Ramadhani Rizky; Ganggi, Roro Isyawati Permata; Budiyanti, Rani Tiyas (Malaysian Journal of Library and Information Science, 2025)
The advancement of contemporary technology requires librarians to continually adapt to manage technology-driven library services. However, technological challenges can cause technostress, which may affect librarians’ performance. Workplace social support is essential in helping librarians cope with technostress. The aim of this study is to determine the role of social support as a coping strategy for technostress among librarians in Indonesian public libraries. This study employed qualitative methods, using semi-structured interviews for data collection. The data were analysed through condensation, presentation, formulation, and validation of findings. This article provides an overview of technostress among librarians in public libraries, their coping mechanisms, and the social support they receive. Librarians cope with technostress through both internal and external mechanisms. Social support as a coping mechanism includes instrumental and emotional support. It is essential for libraries to cultivate a conducive work climate and offer continuous technology training. This study highlights that technostress adversely impacts librarians’ physiology and performance. Therefore, libraries must foster a supportive work environment and provide ongoing technological training.